2021
DOI: 10.1186/s12912-021-00770-5
|View full text |Cite
|
Sign up to set email alerts
|

Negative effects of the COVID-19 pandemic on nurses can be buffered by a sense of humor and appreciation

Abstract: Background The first analyses of the various consequences of the COVID-19 pandemic show that the risk to nurses’ psychological well-being is particularly high. As the pandemic and the demands imposed on nurses are not yet fully understood, there is a need to seek buffering factors to protect nurses’ psychological health. In line with the earliest evidence, we hypothesize pandemic-related increases in perceived stress and decreases in the frequency of flow experiences, likewise in satisfaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 67 publications
4
25
0
Order By: Relevance
“…Coping strategies are important for nurses to handle the COVID-19 pandemic ( Bartzik, Aust & Corinna Peifer, 2021 ). Despite the critical situation, analyses carried out by many researchers all over the world during the COVID-19 pandemic show that nurses have enough resources to employ constructive coping strategies ( Sehularo et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coping strategies are important for nurses to handle the COVID-19 pandemic ( Bartzik, Aust & Corinna Peifer, 2021 ). Despite the critical situation, analyses carried out by many researchers all over the world during the COVID-19 pandemic show that nurses have enough resources to employ constructive coping strategies ( Sehularo et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Juczyński & Ogińska-Bulik (2012a) , humor and venting are less effective in coping with stress, although they are very useful in some situations. On the other hand, Bartzik, Aust & Corinna Peifer (2021) believe that the sense of humor and appreciation are two resources that help nurses deal with the COVID-19 pandemic. Literature data also show that the most common way of reducing negative consequences of distress and maintaining the sense of security is access to reliable information ( Heitzman, 2020 ; Folkman & Moskowitz, 2004 ; Lai et al, 2020 ; Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from Ethiopia showed that 22.9, 19.2 and 28.2% of nurses suffered from depression, anxiety and stress, respectively [ 8 ]. The COVID-19 pandemic heightened the stress levels of health workers, especially nurses [ 18 , 19 ]. Comparatively, nurses felt more stressed during the COVID-19 pandemic than before the pandemic [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic heightened the stress levels of health workers, especially nurses [ 18 , 19 ]. Comparatively, nurses felt more stressed during the COVID-19 pandemic than before the pandemic [ 18 ]. Another study in Portugal reported that COVID-19 led to an increase in the prevalence of depression, anxiety and stress among nurses compared to the general population [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a validated instrument specifically adapted to the work context in which burnout symptoms occur and considers different facets of the flow experience. Also, the Flow Frequency Scale [ 126 , 127 ] is recommended as this instrument addresses three facets of flow—absorption, perceived demands-skill balance, and enjoyment—that integrate the competing operationalizations of flow [ 24 ]. This measurement instrument focuses on the frequency of flow experience and contains one item eliciting whether all three components of the flow occurred simultaneously.…”
Section: Discussionmentioning
confidence: 99%